Kolaborasi Aktor dalam Pembangunan Pariwisata Hutan Mangrove Tongke-Tongke Kabupaten Sinjai, Sulawesi Selatan - Astuti Umar; Burhanuddin Burhanuddin; Nasrulhaq Nasrulhaq (Research and Development Agency Ministry of Home Affairs, 2019)
Collaborative governance process involving actors of Government, private, and community among them DISKAN, DISPARBUD, DLHK, KPSDA-ACI, and communities in the tourism development of Mangrove Forests Tongke Regency Sinjai Tongke to inequality-internal imbalances that are difficult to open, directions of development are stagnant and the limitations of the capabilities managers minimal while the needs of the community will be getting high quality service so that the required motion active actors to move and organize development. The purpose of this study is to find out the collaborative process that occurs in achieving development in an effective, accountable, transparent manner and meeting public needs. This type of research is a qualitative approach is used with type a descriptive study using a kind of case study research. The results showed that prakter collaboration in development of tourism the mangrove forest Tongke-Tongke Regency Sinjai is the right choice this encouraged the actors much easier in doing coordination with units of organization scope Sinjai Regency Government, creation of synergy partisispasi the actors due to the open communication that are able to engender the trust and commitment of the actors to create a sense of equality in addressing problems tourism development of mangrove forests Tongke-Tongke.